Activation of Nurr1 with Amodiaquine Protected Neuron and Alleviated Neuroinflammation after Subarachnoid Hemorrhage in Rats. (10th February 2021) - Chen, Huaijun; Yu, Xiaobo; Hu, Libin; Peng, Yucong; Yu, Qian; Zhou, Hang; Xu, Chaoran; Zeng, Hanhai; Cao, Yang; Zhuang, Jianfeng; Fu, Xiongjie; Zhou, Guoyang; et al.
Abstract : Background . Nurr1, a member of the nuclear receptor 4A family (NR4A), played a role in neuron protection, anti-inflammation, and antioxidative stress in multidiseases. We explored the role of Nurr1 on subarachnoid hemorrhage (SAH) progression and investigated the feasibility of its agonist (amodiaquine, AQ) as a treatment for SAH. Methods . SAH rat models were constructed by the endovascular perforation technique. AQ was administered intraperitoneally at 2 hours after SAH induction. SAH grade, mortality, weight loss, neurological performance tests, brain water content, western blot, immunofluorescence, Nissl staining, and qPCR were assessed post-SAH. In vitro, hemin was introduced into HT22 cells to develop a model of SAH. Results . Stimulation of Nurr1 with AQ improved the outcomes and attenuated brain edema. Nurr1 was mainly expressed in neuron, and administration of AQ alleviated neuron injury in vivo and enhanced the neuron viability and inhibited neuron apoptosis and necrosis in vitro. Besides, AQ reduced the amount of IL-1 β + Iba-1 + cells and inhibited the mRNA level of proinflammatory cytokines (IL-1 β and TNF- α ) and the M1-like phenotype markers (CD68 and CD86). AQ inhibited the expression of MMP9 in HT22 cells. Furthermore, AQ reduced the expression of nuclear NF- κ B and Nurr1 while increased cytoplasmic Nurr1 in vivo and in vitro. Conclusion . Pharmacological activation of Nurr1 with AQ alleviated the neuron injury and neuroinflammation. The mechanism of antineuroinflammation may be associated with the Nurr1/NF- κ B/MMP9 pathway in the neuron. The data supported that AQ might be a promising treatment strategy for SAH.